Endoplasmic Reticulum Stress Disturbs Lipid Homeostasis and Augments Inflammation in the Intestine and Isolated Intestinal Cells of Large Yellow Croaker (Larimichthys crocea) - Fang, Wei; Chen, Qiuchi; Li, Jiamin; Liu, Yongtao; Zhao, Zengqi; Shen, Yanan; Mai, Kangsen; Ai, Qinghui (Frontiers in Immunology, 2021)
The small intestine is crucial for lipid homeostasis and immune regulation of the whole body. Endoplasmic reticulum (ER) stress may affect lipid metabolism and inflammation in the intestine, but the potential mechanism is not completely understood. In the present study, intraperitoneal injection of tunicamycin (TM) induced ER stress in the intestine of large yellow croaker (Larimichthys crocea). ER stress induced excessive accumulation of triglyceride (TG) in the intestine by promoting lipid synthesis. However, it also enhanced lipid secretion and fatty acid oxidation. In addition, ER stress augmented inflammation in the intestine by promoting p65 into the nucleus and increasing proinflammatory gene expression. In the isolated intestinal cells, the obtained results showed that TM treatment significantly upregulated mRNA expression of lipid synthesis and inflammatory response genes, which were consistent with those in vivo. Moreover, overexpression of unfolded protein response (UPR) sensors significantly upregulated promoter activities of lipid synthesis and proinflammatory genes. In conclusion, the results suggested that ER stress disturbed lipid metabolism and augmented inflammation in the intestine and isolated intestinal cells of large yellow croaker, which may contribute to finding novel therapies to tackle lipid dysregulation and inflammation in the intestine of fish and human beings.